Efektivitas Model Pembelajaran Kooperatif Tipe Jigsaw pada Siswa Kelas XI terhadap Hasil Belajar Bahasa Indonesia Materi Makna dalam Pertunjukan Drama di SMAN 6 Lhokseumawe (International Forum of Researchers and Lecturers, 2024)
This research aims to determine the effectiveness of the jigsaw type cooperative learning model for class The research method used is a quantitative method. The data collection technique used is in the form of test questions and observations. The data obtained in this research are the learning results of students at SMAN 6 Lhoksemawe. The sample in this research was all class XI students of SMAN 6 Lhokseumawe. Data analysis techniques in this research use normality tests, homogeneity tests, and hypothesis tests. Based on the research results, it was found that student learning outcomes increased by 61.87% in the medium category. This can show that the jigsaw type cooperative learning model is quite effective.